Primary tubal choriocarcinoma - Nandan, Neetha; Prasad, Kishan; Begum, Mubeena; Rai, Supriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Choriocarcinoma is extremely aggressive form of gestational trophoblastic disease. It occurs due to neoplastic changes in the chorionic villi. The most common site of origin is uterus but rarely can occur in tube, cervix or ovary. Tubal choriocarcinoma may develop either by malignant transformation of a tubal pregnancy or can arise denovo without an ectopic pregnancy. The reported incidence of tubal choriocarcinoma is approximately 1.5/1,000,000 births. Here, we report a case in which salphingectomy was done thinking it was an acute ectopic pregnancy, but histopathological examination showed tubal choriocarcinoma. This tubal choriocarcinoma occurred denovo and was not secondary to an ectopic pregnancy. Patient did not need adjuvant chemotherapy as it was detected early and is being followed up by β-hcg monitoring.